Notions and practices about trash and solid waste management in urban enclosures - Moreno-Ávila, Olga Lucía; Rincón-Salazar, María Teresa (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
This paper analyzes the notions and behaviors about trash by residents of urban enclosures. The text presents theoretical and contextual references in order to show the importance of studying topics such as consumption, trash generation, and environment preservation in an integrated manner. It also summarizes some findings of the qualitative research project called “Social regulation of the behavior of residents in gated communities in Cali”. People who live in gated communities are regulated by the Horizontal Property Law. They share common areas and create different types of relations. The main purpose of this paper is to understand the relations between citizens’ practices in terms of solid waste management and environmental conservation; also, to present guidelines for environmental education interventions.